SECRET IMAGE SHARING SCHEMES THROUGH SIS - Nazima Begum; T. Anita; Prof B V Ramana Murthy (The Bioscan, 2024)
The safeguarding of digitized data against unwanted access and modification has become an issue of utmost importance as a direct result of the rapid development of network technology and internet applications. In response to this challenge, numerous secret image sharing (SIS) schemes have been developed. SIS is a method for protecting sensitive digital images from unauthorized access and alteration. The secret image is fragmented into a large number of arbitrary shares, each of which is designed to prevent the disclosure of any information to the trespassers. In this paper, we present a comprehensive survey of SIS schemes along with their pros and cons. We review various existing verifiable secret image sharing (VSIS) schemes that are immune to different types of cheating. Additionally, we discuss steganography techniques that hide secret information within digital images and Shamir secret sharing, which divides a secret into multiple parts, with a threshold number of parts required to reconstruct the secret. We have identified various aspects of developing secure and efficient SIS schemes, including steganography and Shamir secret sharing. In addition to that, a comparison and contrast of several SIS methodologies based on various properties is included in this survey work. We also highlight some of the applications based on SIS. Finally, we present open challenges and future directions in the field of SIS.